2020
DOI: 10.3389/fped.2020.576270
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors and Reasons for Discharge Against Medical Advice for Newborns With Neonatal Surgical Diseases: A Preliminary Study From a Tertiary Care Hospital in Beijing, China

Abstract: Background: To identify the risk factors and reasons for discharge against medical advice (DAMA) for newborns with neonatal surgical diseases in a tertiary care hospital in China. Methods: A retrospective study was conducted on all newborn patients admitted to the neonatal surgery department of Beijing Children's Hospital between January 1, 2016 and January 1, 2020. Medical records were compared between DAMA and non-DAMA patients. Univariate and multivariate logistic regressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…This finding is similar to the 22.24% and 25.4% reported from NICUs in India [ 12 , 13 ] but higher than Nepal (18%) [ 1 ] and Nigeria (11.2%) [ 3 ]. Emergency admission and admission to the neonatal intensive care unit itself was reported as a significant independent risk factor for DAMA [ 2 , 8 ]. Prejudiced decision making by the family members contributed to increase DAMA among neonates [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This finding is similar to the 22.24% and 25.4% reported from NICUs in India [ 12 , 13 ] but higher than Nepal (18%) [ 1 ] and Nigeria (11.2%) [ 3 ]. Emergency admission and admission to the neonatal intensive care unit itself was reported as a significant independent risk factor for DAMA [ 2 , 8 ]. Prejudiced decision making by the family members contributed to increase DAMA among neonates [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…DAMA is a major challenge for hospital treatment teams and it is practically common in all medical facilities and difficult to eliminate leading to unpredictable complications [ 2 ]. PNA, sepsis and prematurity without complications were the most common diagnoses in DAMA neonates.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studying the local neonatal disease spectrum is important for the prevention and treatment of neonatal disease. However, to date, reports have mainly focused on the developed areas of China, such as Beijing (5), Hefei (6), Changsha (7), and Shanghai (8). These studies found that the types, order and mortality rate of diseases change over time, and reported that gestational age (9)(10)(11)(12)(13) and birth weight (14)(15)(16) are significantly correlated with neonatal diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Infants born at less than 32 weeks (very preterm infants, VPIs) account for about 15-16% of all preterm births, with the highest mortality and morbidity rates (1,2). In China and many other middle-or low-income countries, it has been reported that discharge against medical advice (DAMA) contributes significantly to the high mortality and morbidity of VPIs (3)(4)(5)(6)(7)(8). DAMA refers to a situation wherein parents terminate treatment before the treating physicians recommend discharge.…”
Section: Introductionmentioning
confidence: 99%